INVESTMENT POLICY FOR RISK PREVENTION IN FOOD ENTERPRISES - LAGODIIENKO, Volodymyr; NIKOLIUK, Olena; SAVCHENKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article is devoted to forming an investment policy for risk prevention in food enterprises. Its aim is to analyze and improve the existing theoretical and methodological framework for risk management and the development of an investment policy for risk prevention in food industry enterprises.The article defines risk as uncertainty, income variability, and the probability of partial or complete loss of invested resources. Investment risk, in turn, represents uncertainty related to the possibility of actual results deviating from planned outcomes due to the influence of various factors. Investment risk can manifest as a loss of profit, capital, or other financial resources resulting from unfavorable economic, financial, or managerial decisions. The study examines the prerequisites for managing investment risks in food industry enterprises in a modern economy characterized by high turbulence, globalization challenges, and digital transformation.The research systematizes investment risks based on their sources, including financial, technological, market, regulatory, organizational, personnel, and environmental risks that directly arise in the operations of food industry enterprises. It is determined that to minimize investment risks, food industry enterprises need to develop and implement an effective risk prevention policy based on applying modern risk management methodologies and adopting innovative approaches to investment decision-making.In an unstable market environment, food industry enterprises are recommended to apply investment asset diversification, currency risk insurance, market trend forecasting, digital tool implementation for management process optimization, corporate culture development, and the integration of sustainable practices. The proposed measures within the investment policy for risk prevention will enhance the resilience of food industry enterprises to external challenges, ensure the effectiveness of investment activities, and contribute to achieving the strategic goals of sustainable development.
Keywords: investment policy; investments; risks; risk prevention; risk management; food enterprise; food industry enterprise